A STUDY OF PHYSICOCHEMICAL PARAMETERS AND HEAVY METALS CONCENTRATION LEVELS IN ORIKUMI LAGOON, VLORA, ALBANIA - Tahiri, Valbona; Denaj, Astrit; Bakaj, Aurora; Vullkaj, Ilir; Musli, Fatjon (MATTER: International Journal of Science and Technology, 2019)
During this study we measured physicochemical parameters (T°C, pH, TDS, EC, Salinity) in situ by a multi parameter portable HI 9829 Hanna and also the concentration levels of heavy metals (cadmium, lead, iron and copper) were given by flame atomic absorption spectrometry in lagoon waters of Orikum, Vlora, Albania. On the basis of obtained data of the physico-chemical and spectrometric measured in water we found a slight variability in salinity, pH near neutrality with a low mobility of metals (except Fe) and elevated TDS and EC at stations mainly S4 and S5 subject to the direct influence of temperatures waters and discharges of wastewater from The Pashaliman Base (A Military Base of Vlora District). The contents of heavy metals concentrations in relation to maximum value are following this trend: Fe>Cd>Pb>Cu. Also, the values of standard deviations of Fe are highest which led to a totally heterogenous distribution.